Estudio del efecto coarticulatorio en el habla - Martínez Licona, A. E.; Martínez Licona, F. M.; Vidal Cabrera, O. O.; Goddard Close, J. C. (Revista Mexicana de Ingenieria Biomedica, 2004)
Speech production is a complex process for study; among the approximations implemented, the spectrographic one shows characteristics that may reflect important differences in speech signals. One of these characteristics is coarticulation which shows acoustic variations easily identified, but at the same time, hardly described in an automatic speech recognition frame. This is a study of the coarticulatory effect in Spanish speech. From the coarticulation definition and a brief explanation of spectral representation, pronunciation characteristics of Spanish speakers from Latin America are shown as well as pronunciation differences in statements of Latino40 database.